Sexual and reproductive health in adolescents belonging to medical office 59, Policlínico Luis Agusto Turcios Lima - del Campo Martínez, Sissy; Pereda Rodríguez, Yoelys; Álvarez Quiñones, Kenia; Díaz Calzada, Marvelia; Ortega Rabi, Yeili (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Sexuality education is a responsibility of society as a whole, it begins at birth within the family group and continues throughout life in the successive links that people establish when interacting with different groups. Objective: to determine the sexual and reproductive health of adolescents belonging to medical office 59, Policlínico Luis Agusto Turcios Lima from July to December 2022. Methods: An observational, descriptive and cross-sectional research was carried out, the universe was represented by a total of 84 adolescents from the medical office and the sample of 56 adolescents between 11 and 19 years of age was selected through intentional sampling according to inclusion criteria. Theoretical, empirical and descriptive statistical methods were used. Results: 58% of the adolescents were female, 62.5% in the 13 to 14 years age group, 91.6% identified parents as the main source of information on sexual and reproductive health, 86% identified AIDS and 53% syphilis as the most frequent sexually transmitted infections, and 97% identified condoms as the most used contraceptive method in the prevention of sexually transmitted infections and pregnancy at this age. Conclusions: the knowledge of adolescents is adequate and corresponds to their behavior.